Iratxe : la organización navarra antifranquista olvidada (1963-1965) - Mikel Bueno Urritzelki (Amnis)
This article approaches the sort history of the navarrese anti-Franco organization Iratxe, who developed a propagnda activity for a period of less tan two years, before joining ETA. It´s anorganization of which there has been little direct documentation and the existing indirect documentation is very scare. In this work the ideology that Iratxe had, the different actions he carried out, is exposed, as well as the contacts mainteined with other basque organizations, such as ETA or the PNV. The difficulty in researching Iratxe is accentuated by the small number of existing sources, which are only limited to a meager original documentation that has been found after searching several archives.